2018
DOI: 10.1111/1747-0080.12422
|View full text |Cite
|
Sign up to set email alerts
|

Use of hand grip strength in nutrition risk screening of older patients admitted to general surgical wards

Abstract: HGS was not found to be suitable in screening older inpatients for malnutrition during admission to surgical wards. As such, screening for nutrition risk using an existing validated tool to identify patients for further in-depth nutritional assessment by an appropriately trained clinician remains the preferred method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
16
0
3
Order By: Relevance
“…However, there is debate regarding the relationship between HGS and nutritional status. Some studies have advocated for the added value of HGS in nutritional assessment [33,34], while others, including the current study, provide evidence that HGS may be of limited use as a predictor of nutritional status [35][36][37]. A recent study showed that HGS and knee extension strength (KES) have moderate-to-low agreement, indicating that HGS should not be used to represent overall muscle strength [38].…”
Section: Discussionmentioning
confidence: 81%
“…However, there is debate regarding the relationship between HGS and nutritional status. Some studies have advocated for the added value of HGS in nutritional assessment [33,34], while others, including the current study, provide evidence that HGS may be of limited use as a predictor of nutritional status [35][36][37]. A recent study showed that HGS and knee extension strength (KES) have moderate-to-low agreement, indicating that HGS should not be used to represent overall muscle strength [38].…”
Section: Discussionmentioning
confidence: 81%
“…Using established HGS cutpoints, sensitivity (SE) and specificity (SP) were inadequate when compared with the SGA (Giulani et al: SE = 0.42, SP = 0.73; Sallinen et al male: SE = 0.88, SP = 0.25; Sallinen et al female: SE = 0.86, SP = 0.21; Alley et al male: SE = 0.59, SP = 0.63; Alley et al female: SE = 0.70, SP = 0.46) . This is consistent with a recent attempt to determine the validity of HGS when compared with the criterion of patient‐generated SGA in surgical patients; HGS also did not enhance the discriminatory value of the Malnutrition Screening Tool …”
Section: Discussionmentioning
confidence: 99%
“…The participants used in these analyses did not have dementia or delirium. Prior work suggests that mental capacity is required for completion of HGS, and approximately 10% of surgical patients are unable to do HGS due to this reason . Other limitations include the potential for interrater differences within and between sites when assessing HGS and 5m; interrater reliability analyses were not conducted due to geographic restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Byrnes et al, who studied older adults admitted to general surgical wards, concluded that grip strength was not "suitable for screening older inpatients for malnutrition". 40 Although finding a significant association between grip strength and nutritional status, McNicholl described grip strength as having "poor validity as a single nutrition indicator". 41 As more of the patients they tested completed a grip strength assessment (92%) than a 5 meter walking assessment (43%), they concluded that grip strength "is a more useful functional measure" than the 5 meter walk test.…”
Section: Grip Strength As a Biomarker Of Current Statusmentioning
confidence: 99%